Intensity distribution and spectral degree of coherence for array beams in non-Kolmogorov atmospheric turbulence. Issue 7 (11th April 2016) - Pan, P.; Liu, G.; Liu, Z.; Wang, Y.; Gu, G.
Abstract : The propagation expressions of the intensity distribution and the spectral degree of coherence for radial array Gaussian Schell-model beams in non-Kolmogorov atmospheric turbulence have been derived. There exists a maximum of the on-axis intensity for radial array beams on propagation. The optimal propagation distance where the maximum appears has been analyzed in detail. The influence of the generalized structure constant and the initial spatial coherence parameter for the correlated superposition beam is different from the uncorrelated one. In particular, the on-axis intensity maximum exhibits a minimum when the generalized exponent α = 3.1. The spectral degree of coherence for the correlated superposition beam is larger than the uncorrelated one, and the difference between the two superposition styles becomes larger when the spatial coherence parameter becomes larger and the turbulence becomes weaker. Moreover, when α = 3.1 the spectral degree of coherence exhibits a minimum.